Study of Ionospheric Variability During Super Substorms - Pandit, D.; Chapagain, N. P.; Adhikari, B. (Journal of Nepal Physical Society, 2020)
This paper study variability of three ionospheric parameters foF2, h′F and hmF2 to investigate the middle latitude ionospheric effect at Boulder, Colorado, USA (40°N, l105.0° W) during super substorms (SSSs) of 24 August 2005, and 7 September 2017 and 8 September 2017 respectively. Continuous wavelet transform (cwt) implemented to identify the low and high frequency and longer and shorter duration present in the signal. The result shows decrease in foF2 during SSSs of 24 August 2005 and 8 September 2017 and increase in foF2 during 7 September 2017. The highest fluctuation in h′F is noticed during SSS of 24 August 2005. The cwt shows that the coupling between solar wind and magnetosphere occurs between ~ 16 to 32 minutes for SSS of 24 August 2005 and between 27.9 to 64 minutes during super substorm of 7 and 8 September 2017 for all the ionospheric parameters respectively. This study leads to understand the impact of SSSs on communication signals due to energy injected in ionosphere during the coupling mechanism between magnetosphere-ionosphere.